China's Economic Diplomacy Strategies: An Analysis of the Belt and Road Initiative in Southeast Asian Countries - Vajrin, Olivia (FIA Unkris Press, 2024)
The BRI is an investment programme in the aspects of development and infrastructure led by China and the countries involved. There are certainly 8 countries in Southeast Asia involved in the cooperation and 4 countries that will be analysed for comparison, namely Thailand, Indonesia, Vietnam and the Philippines. The involvement of these 4 countries in BRI is a big question, namely how the economic diplomatic strategy carried out by China towards these countries so that they want to establish BRI cooperation with China. Therefore, this study will analyse the differences in China's economic diplomacy strategies through BRI towards four Southeast Asian countries that have different backgrounds. In addition, this study will also analyse the impact of BRI cooperation on these countries. This study will use economic diplomacy because it can help analyse the economic diplomacy strategy carried out by China through the BRI to achieve its national interests. This study uses the literature study method and comparative analysis using qualitative data. The results of this study show that there are different strategies and approaches to economic diplomacy by China through BRI to Thailand, Indonesia, Vietnam and the Philippines and they have different assessments regarding the impact of BRI.